The Use Of Maritime English In The Daily Report By Indonesian Maritime Students - Aprillina, Aprillina; Suryaningsih, Encis Indah (Universitas Maritim AMNI Semarang, 2024)
Maritime English as the variety of ESP is taught for the students in the maritime field. In this study mainly discuss about the understanding of the Indonesian maritime students in using maritime English in the daily report in form in cadet record book. The students are expected to understand in using maritime English in the daily report the appropriate approach. The communicative approach has been selected as the best approaches since it involved the student’s activities in practice and drills the tasks in using maritime English in daily report. In this case, the teachers are expected to be aware with the student’s background of knowledge. The teachers are also expected to have communicative approach in order to discover the best implementation of the communication aims.